In-medium modification of dijets in PbPb collisions at root s(NN)=5.02 TeV - Sirunyan, A. M. (2021)
Modifications to the distribution of charged particles with respect to high transverse momentum (p(T)) jets passing through a quark-gluon plasma are explored using the CMS detector. Back-to-back dijets are analyzed in lead-lead and proton-proton collisions at root s(NN) = 5.02 TeV via correlations of charged particles in bins of relative pseudorapidity and angular distance from the leading and subleading jet axes. In comparing the lead-lead and proton-proton collision results, modifications to the charged-particle relative distance distribution and to the momentum distributions around the jet axis are found to depend on the dijet momentum balance x(j) , which is the ratio between the subleading and leading jet p(T). For events with x(j) approximate to 1, these modifications are observed for both the leading and subleading jets. However, while subleading jets show significant modifications for events with a larger dijet momentum imbalance, much smaller modifications are found for the leading jets in these events.